Effect of hormone replacement therapy on amyloid beta (Aβ) plaque density in the rhesus macaque amygdala - Appleman, Maria-Luisa; Thomas, Jeremy L.; Weiss, Alison R.; Nilaver, Benjamin I.; Cervera-Juanes, Rita; Kohama, Steven G.; Urbanski, Henryk F. (Frontiers in Aging Neuroscience, 2024)
Background Amyloid beta (Aβ) plaque density was examined in the amygdala of rhesus macaques, to elucidate the influence of age, diet and hormonal environment. Methods Luminex technology was used to measure cerebrospinal fluid (CSF) concentrations of Aβ40 and Aβ42 across three decades, while immunohistochemistry was used to examine Aβ plaque density in the amygdala. Results Aβ40 was found to be the predominant isoform of Aβ in the CSF, but neither Aβ40 or Aβ42 concentrations showed an age-related change, and the ratio of Aβ42 to Aβ40 showed only a marginal increase. Significantly fewer Aβ plaques were detected in the amygdala of old ovariectomized animals if they received estradiol HRT (p < 0.001); similar results were obtained regardless of whether they had been maintained on a regular monkey chow for ∼48 months or on a high-fat, high-sugar, Western-style diet for ∼30 months. Conclusion The results demonstrate that HRT involving estrogen can reduce Aβ plaque load in a cognitive brain region of aged non-human primates. The results from this translational animal model may therefore have clinical relevance to the treatment of AD in post-menopausal women, whether used alone, or as a supplement to current pharmacological and monoclonal antibody-based interventions.